Effect of Quality of Irrigation Water on Dry Matter Production, and on Calcium, Magnesium and Phosphorus Content of Wheat, Barley and Pea - Khan, M Usman; Saxena, S N (Annals of Arid Zone, 2016)
The effect of variation in conductivity, SAR values and. boron content of applied irrigation water was evaluated for wheat, barley and pea. In aU the three crops increasing levels of conductivity, SAR and boron suppressed the dry matter production. Calcium absorption was increased in all the three crops with an increase in conductivity. Magnesium absorption also increased in wheat and pea but an antagonistic trend was recorded in case of barley. Phosphorus content of pea and wheat increased with increase in conductivity,SAR and boron levels. Increasing SAR values of irrigation water resulted in decreased calcium and magnesium absorption in wheat and barley but reverse was true in case of pea. Increasing levels of boron in irrigation water suppressed calcium absorption in wheat and pea but increased the same in barley. A reverse trend was observed with respect to magnesium. All first order interactions have produced significant changes in plants.